Psyche-Image; or Truth in the Infinitive. Issue 3 (4th May 2019) - Pyle, Forest
ABSTRACT: This essay takes "Ode to Psyche" as its point of departure to explore the "auratics of agnosticism, " an aesthetics of affective disbelief that runs from Shelley and Keats through Pater and Wilde. Keats's ode to this neglected and belated goddess crystallizes the temporal suspension of Romantic agnosticism. About half-way through De Profundis, Oscar Wilde writes that he would like to "found an order for those who cannot believe: the Confraternity of the Fatherless one might call it, where on an altar, on which no taper burned, a priest, in whose heart peace had no dwelling, might celebrate with unblessed bread and a chalice empty of wine . . . Agnosticism should have its ritual no less than faith. It has sown its martyrs, it should reap its saints." "Ode to Psyche" proposes just such a priest in this transfigured form of the Pindaric ode, one that creates a new poetic "dwelling" for the "shadowy thought" of a devoted but unbelieving apostle. Wilde called this "pale-mouth'd prophet" the "preacher of vague and unreal things, " one who builds an auratic temple of disbelief that remains a shrine of Romantic aesthetics.